Moderating Role of Governance in Growth-Technology-Environment Nexus: Evidence from Developing Economies - Fazal, Snober; Azam, Ali (iRASD Journal of Economics, 2023)
Competition among economies to attain maximum economic growth has led to environmental degradation. At the same time, technological innovations are empirically validated for having a role in achieving sustainable development. Good governance could make appropriate measures to design frameworks, develop instruments, and set targets to protect the environment. The current study intends to check the nexus among technological innovations, energy consumption, economic growth, and environmental degradation for a panel of 40 developing countries. The panel data of developing economies for a period of 25 years (from 1996 to 2020) was collected. The relationship was theoretically and econometrically modeled and finally analyzed using the dynamic panel Generalized Method of Moments (GMM). The empirical results of the dynamic panel GMM technique reveal significant and insightful relationships between the variables and their impact on environmental degradation (CO2 emissions). Technological innovations and renewable energy consumption negatively affect CO2 emissions, while economic growth, financial development, and globalization have positive effects. By moderating the growth-technology-environment nexus, governance enhances the positive impact of technological innovations and renewable energy consumption while mitigating the adverse effects of economic growth on CO2 emissions. These findings have important implications for policymakers addressing environmental issues and promoting sustainable development.